Disposable ion-selective electrodes - Borchardt, Michael; Dumschat, Christa; Cammann, karl; Knoll, Meinhard (Sensors and actuators. B, Chemical, 1995)
In this paper we describe a low-cost ion-selective electrode in double matrix membrance technology. This sensor is prepared from filter paper with an evaporated silver conducting line on one side. For insulation the sensor is laminated with a preperforated heat-sealing film. A coated film sensor in double matrix membrane technology is produced by filling one hole with a defined volume of an ion-selective polymer matrix membrane cocktail. The double matrix membrane (DMM) is formed by the polymer matrix membrane and the additional microfibre matrix (MFM) of the filter paper. Such sensors can be produced in a batch process. Therefore mass-production of low-cost sensors is possible. The response behaviour of the low-cost ion-selective electrode is comparable to that of conventional macro ion-selective electrodes.